A descriptive survey on garment care label usage - Hervosa, Krystel Gayl P. (College of Home Economics, University of the Philippines, 2009)
This study investigated the care label usage of female consumers. It determined if female consumer respondents understand the garment care label's function and symbols. This study also identified if the respondents follow the garment care labels instructions. Likewise, the problems encountered by respondents when handling care labels were determined. This research contributed new data that can be used for possible evaluation and implementation of regulations regarding garment care labeling. This study also identified the need for consumer education regarding acre labels. Descriptive method of research was used in this study. The instrument employed for data collection was questionnaire. It used purposive and convenience sampling in choosing the respondents. There were total of 30 female respondents (15 administrative staff and 15 faculty members) from the College of Home Economics, University of the Philippines Diliman who participated in the study. The data gathered from the survey were classified quantitatively and qualitatively. In the quantitative analysis, data were tallied, tabulated and graphed. For the qualitative analysis, data were categorized, summarized, and interpreted. Frequency distribution, percentage and ranking were used. The frequency and percentage were utilized t6o show the distribution of respondents' response while ranking was done by positioning their frequencies from highest to lowest. Findings of the study showed: first, the respondents are familiar to care labels and they understand its function; second, respondents only understand the instructions indicated in the acre labels if it is written in words, they are confused with the meaning of care label symbols; third, majority of the respondents check the care label of their garments before washing but they do not follow the care instruction all the time. Based from these data, it van be concluded that there is a need for consumer education. Furthermore, respondents experienced many problems when handling garment care label. Most of them agreed that they do not understand the care label symbols, unless accompanied by descriptions. Other problems they experienced include fading acre labels, unreadable font size, presence of unfamiliar terms, written in foreign language, insufficient information is provided, and some times caused skin irritation. Even though not directly connected in the handling of garment care label, respondents added other problems they have observed in relation to the topic. They mentioned that majority of the garments sold in the local market do not have care labels. Likewise, fabrics do not come with care labels, only finished garments. Based from this information, the government shall review the status of garment care labeling rule in the country. A law regulating the care labeling in the country shall be imposed. It was recommended that while garment care labeling rule is not yet implemented, the best thing to do is to conduct a consumer education. A broader and in depth study of this research shall also be done.